The Effect of Providing Online Ticket Reservation Services Through Traveloka on Passenger Repurchase Interests at Yogyakarta International Airport - Wiguna, Veronica Laras Ati; Rachmawati, Desiana (CV. Rayyan Dwi Bharata, 2023)
In the web-based ticket reservation framework through the Traveloka application, purchasers can make flight ticket reservations whenever and anyplace with a quick time so buyers will get back to utilizing the help when they are fulfilled. The purpose of this study is to ascertain whether or not Traveloka's online ticket reservation service at Yogyakarta International Airport has an impact on passengers' intentions to repurchase tickets.100 people take part in this study's sampling. A questionnaire is used in this study to collect data. The data analysis strategy makes use of the T test, Coefficient of Determination (R2), and Descriptive Test from simple linear regression analysis.The findings of the study indicate that the variable offering online ticket reservation services through Traveloka has a positive effect on passenger repurchase intentions at Yogyakarta International Airport, as its regression coefficient value is 0.877. The determined T esteem is 10,576 with an importance worth of 0.000 0.05 which shows that Ho is dismissed and Ha is acknowledged. The fact that the significant value is less than 0.005 indicates that Traveloka's provision of online ticket reservation services has a positive impact on passenger intent to repurchase tickets. The coefficient of determination is 0,528; consequently, Passenger Interest (Y) is influenced by the variable Service Provision (X) by 51.8 percent, while other variables not included in the research model are responsible for the remaining 47.2 percent. The engaging test shows that Help Arrangement (X) is 55,73. The typical worth of Traveler Interest (Y) is 55,24. The results of the hypothesis testing indicate that passengers at Yogyakarta International Airport are more likely to repurchase their tickets if they can book them online using the Traveloka app. This is built up by certain respondents communicating their arrangement.